Studies on effect of Tongfengxiaofang in HUM model mice using a UPLC–ESI–Q‐TOF/MS metabolomic approach. (3rd May 2021) - Chen, Renhao; Wang, Qi; Li, Zhifeng; Wang, Dongxu; Yang, Shilin; Feng, Yulin
Abstract: Hyperuricemia (HUM) is a major risk factor for the development of gout. The traditional Chinese medicine (TCM) complex prescription Tongfengxiaofang (TFXF) is composed of a variety of TCMs. To study the therapeutic effect of TFXF on HUM mice and the mechanisms by which it exerts a therapeutic effect, the biochemical indices were measured and qPCR technique was used. In addition, plasma metabolomics analysis was carried out based on UPLC–Q‐TOF/MS to evaluate the characteristics of the metabolic spectrum changes. TFXF significantly downregulated the contents of uric acid, urea nitrogen and creatinine in serum and the concentration of xanthine oxidase in liver of HUM mice. In addition, TFXF significantly inhibited the overexpression of uric acid transporter 1 and glucose transporter 9 and upregulated the expression of organic anion transporter 1 in the kidney. A total of 152 metabolites were identified and 11 key biomarkers were further selected from these pathways to understand the mechanism of TFXF on the arginine biosynthesis, galactose metabolism, pyrimidine metabolism, glycerophospholipid metabolism, tryptophan metabolism and the citrate cycle (TCA cycle). The results of this confirmed the effect of TFXF on HUM and revealed the metabolic activity mechanism.